Uji Kegunaan Perangkat Lunak menggunakan Metode Cognitive Walkthrough - M. Rifky Naratama Susanto; Annisa Adytia Putri; Muh. Andriansya Azhari; Lutfi Rahmatuti Maghfiroh (Politeknik Statistika STIS, 2021)
Professional Placement (PKL) Politeknik Statistika STIS batch 60, especially the Communication and Collaboration Systems division (Sikoko) designed a web-based online discussion forum to meet the needs of activity, a discussion forum when PKL is ongoing. This raises a problem regarding the web display that must be made according to users, college student. If the web display is not user-friendly, it will certainly prevent users from using the forum. Research on the user interface design of the PKL web Forum was carried out using one of the usability analysis methods, namely Cognitive Walkthrough (CW). The results of usability testing with the Cognitive Walkthrough method on the PKL 60 Web Forum were tested by running scenarios of the main tasks performed on the forum, such as creating a thread, replying to a thread, and searching for certain threads. The results show a decrease in the error rate and an increase in the completion rate by respondents after testing and repairing the web display.